2019
DOI: 10.1126/science.aav6202
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale ruminant genome sequencing provides insights into their evolution and distinct traits

Abstract: The ruminants are one of the most successful mammalian lineages, exhibiting morphological and habitat diversity and containing several key livestock species. To better understand their evolution, we generated and analyzed de novo assembled genomes of 44 ruminant species, representing all six Ruminantia families. We used these genomes to create a time-calibrated phylogeny to resolve topological controversies, overcoming the challenges of incomplete lineage sorting. Population dynamic analyses show that populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
307
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(366 citation statements)
references
References 184 publications
25
307
2
Order By: Relevance
“…Our reindeer genome assembly is 2.66 Gb in size and represents ~91% of the estimated 2.92 Gb genome size according to the k-mer analysis. The estimated genome size of reindeer in our study is slightly higher than that in two recent studies, i.e., 2.86 48 19 ). In addition, the number of protein-coding annotated genes (>27,000) in our genome assembly draft is higher than that typically predicted in the latest assemblies of several other domesticated mammalian species (~21,000) [18][19][20]25,33 and in the first genome draft of reindeer (21,555) 21 .…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Our reindeer genome assembly is 2.66 Gb in size and represents ~91% of the estimated 2.92 Gb genome size according to the k-mer analysis. The estimated genome size of reindeer in our study is slightly higher than that in two recent studies, i.e., 2.86 48 19 ). In addition, the number of protein-coding annotated genes (>27,000) in our genome assembly draft is higher than that typically predicted in the latest assemblies of several other domesticated mammalian species (~21,000) [18][19][20]25,33 and in the first genome draft of reindeer (21,555) 21 .…”
Section: Discussioncontrasting
confidence: 80%
“…Our phylogeny suggests that reindeer diverged from four other domestic ruminants ca. 36 million years ago, which is earlier than previously estimated 21,48 . The demographic analysis (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, bones of leopard ( Panthera pardus ) have been found associated with hunting by prehistoric humans throughout Europe (reviewed by Sommer & Benecke, ). Additionally, the decline of ruminants since 100–50 kya has been partially attributed to human activities, rather than climatic oscillations (Chen et al, ), and hence the lynx decline during the Late Pleistocene could also be indirectly attributable to humans through negative effects on prey. Our hypothesis is in line with previous work that supports the idea that anthropogenic impacts in combination with climatic oscillations were one of the main drivers of the decline, and in some cases the extinction, of fauna and flora during the Late Pleistocene and early Holocene (Braje & Erlandson, ; Chen et al, ; Gretzinger et al, ; Lorenzen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A major goal of evolutionary biology is to elucidate the genomic underpinnings of phenotypic innovations across the tree of life. Over the past decade, comparative genomics has been used as a powerful tool to begin to elucidate the genetic basis of phenotypic innovations and adaptation in a wide range of organisms (Xu et al 2017;Gou et al 2014;Zhang et al 2014;Chen et al 2019;Exposito-Alonso et al 2018;Gaither et al 2018;Goodman et al 2009;Wang et al 2019;Wu et al 2014). These studies have often identified changes in gene repertoire (e.g., expansions of certain gene families) or genomic signatures of molecular evolution at orthologous genes, by comparing the genomes of species with and without a phenotype of interest (Xu et al 2017;Gou et al 2014;Gaither et al 2018;Goodman et al 2009;Wang et al 2019;Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%